2020
DOI: 10.1016/j.tics.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Control over Representational States in Working Memory

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. • Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 136 publications
(195 reference statements)
13
129
0
Order By: Relevance
“…Here, we showed the modulation of alpha lateralisation across somatosensory and parieto-occipital regions when the participants directed attention to the relevant responses according to the comparisons between the tested and maintained information. These results support the notion that alpha lateralisation may reflect a general mechanism that determines the engagement and disengagement of the cortices according to the task relevancy across various sensory modalities and controls the representational states of WM (de Vries, Slagter, & Olivers, 2020;Klimesch, 2012;Kuo, Li, Lin, Hu, & Yeh, 2017;van Ede, 2018;Wallis, Stokes, Cousijn, Woolrich, & Nobre, 2015). We showed that temporal predictability can optimise attentional prioritisation and the selection of responses, thereby bringing alpha lateralisation forward when the probe onset was highly predictable.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we showed the modulation of alpha lateralisation across somatosensory and parieto-occipital regions when the participants directed attention to the relevant responses according to the comparisons between the tested and maintained information. These results support the notion that alpha lateralisation may reflect a general mechanism that determines the engagement and disengagement of the cortices according to the task relevancy across various sensory modalities and controls the representational states of WM (de Vries, Slagter, & Olivers, 2020;Klimesch, 2012;Kuo, Li, Lin, Hu, & Yeh, 2017;van Ede, 2018;Wallis, Stokes, Cousijn, Woolrich, & Nobre, 2015). We showed that temporal predictability can optimise attentional prioritisation and the selection of responses, thereby bringing alpha lateralisation forward when the probe onset was highly predictable.…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, shifts of attention toward a lateralized target resulted in a contralateral decrease in alpha power, whereas shifting attention away from a lateralized distractor resulted in a contralateral increase in alpha power. The pattern of results support the notion that alpha lateralization mediates the task-dependent prioritization and de-prioritization of items within working memory 36 . In addition, we strengthen the previous claim that auditory alpha lateralization is absent when spatial information is task-irrelevant 8,44 .…”
Section: Resultssupporting
confidence: 78%
“…Accordingly, both behavioral as well as neural evidence question the notion that an active inhibition mechanism completely deteriorates the non-cued item: On a behavioral level, using a series of cues, it has been shown that originally cued and then defocused items remain strengthened and result in faster and more accurate performance compared to trials in which a previously un-cued item (and thus "un-strengthened" item) is probed. In addition, EEG studies cast doubt on whether alpha lateralization actually mediates potential distractor exclusion effects 35,36 : For instance, Noonan and colleagues failed to find a lateralization of alpha power in response to a pre-cue indicating the location of an upcoming distractor, although, on the behavioral level, clear reaction time and accuracy improvements provide evidence for effective distractor exclusion (see also de Vries et al 37 ). However, it should be considered that the latter findings refer to anticipatory suppression of distractors in the visual domain, whereas the present study deals with the inhibition of previously relevant information within auditory working memory that subsequently becomes irrelevant.…”
Section: Alpha Lateralization As a Proxy Of Target Prioritization Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed activity patterns were in the alpha and beta ranges, frequency ranges that are critical for maintenance of visual information. Alpha enhancement likely reflects inhibition of information that could interfere with maintenance, while beta activity is related to controlling the information that is being actively maintained 51 . The early delay activity was followed by a period of desynchronous activity for the remainder of the delay which may suggest preparation for the upcoming response 52 .…”
Section: Methodsmentioning
confidence: 99%